Building a more sustainable landscape, Together - Center for International Forestry Research (Center for International Forestry Research, 2021)
The Center for International Forestry Research (CIFOR) is working together with public and private stakeholders in the Kwaebibirem-Atiwa landscape to co-design a Landscape Development Strategy that will support coordinated planning and action towards more sustainable and people-centred commodity production.